Adiabatic perturbation theory for Van der Waals coefficients - Görling, Andreas; Heinze, H.H.; Levy, Mel (Journal of Molecular Structure-Theochem, 2000)
The leading contribution to the Van der Waals C coefficient in an expansion with respect to the coupling strengths of the electrons is derived in terms of the Kohn-Sham (KS) orbitals and eigenvalues, and evaluated for noble gases and small molecules. (C) 2000 Published by Elsevier Science B.V.